2016
DOI: 10.1007/s11655-016-2095-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zuogui Pill (左归丸) on monoamine neurotransmitters and sex hormones in climacteric rats with panic attack

Abstract: Pretreatment with ZGP in climacteric rats may improve the behavior of panic attack, which may be related to increased 5-HT and NE in the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Morris water maze test indicated that ZGP could repress the damage of MCAO/R by inhibiting escape latency and improving the percentage of time spent in the target quadrant. In a publication of Li and Wang [29], the treatment with ZGP in climacteric rats can recover the behavior from panic attacks. Another study reports that ZGP has protective effects on rat optic nerve [30].…”
Section: Discussionmentioning
confidence: 99%
“…Morris water maze test indicated that ZGP could repress the damage of MCAO/R by inhibiting escape latency and improving the percentage of time spent in the target quadrant. In a publication of Li and Wang [29], the treatment with ZGP in climacteric rats can recover the behavior from panic attacks. Another study reports that ZGP has protective effects on rat optic nerve [30].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, ZGW is associated with many neuro-systemic disorders. According to a study on monoamine neurotransmitters in climacteric rats, the treatment of ZGW apparently decreases the time spent in elevated T-maze and the levels of 5-hydroxytryptamine and noradrenalin, indicating ZGW may participate in the nerve conduction [13]. Another study by Wang et al [14] proposes ZGW has protective effects on retina ganglion cells after optical nerve clipping contusion in rats.…”
Section: Introductionmentioning
confidence: 99%